Dynamiques urbaines et mutations des espaces agricoles en Languedoc-Roussillon (France) - Patricia Abrantes (Unité Mixte de Recherche 8504 Géographie-cités, 2010)
Languedoc-Roussillon is a region of France where rural and urban areas have historical links based on wine economy. In recent years, this Mediterranean region has seen major urban transformations, affecting land use in a rapid manner, mostly in terms of farming land. These changes are characterized by the increasing urban contiguity in coastal areas, urban sprawl and dynamics of metropolitan characteristics between the cities of Montpellier and Nîmes. We propose a methodology to increase our knowledge of current urban dynamics, and especially the spatial relationships and structures resulting there from. The above said methodology therefore includes analysis and modelling of spatial changes at a regional scale. The results are sorted in a typology of urban dynamics. This typology is crossed with the spatial analysis of the transformations of land use, especially in areas where the mutations of agricultural, forest and artificial soils are most important. This crossed analysis between urbanisation and mutations of farming land aims at contributing to an integrated and systemic geographical knowledge of the changes in land use at regional scale. These results could be of use in supporting a prospective reflection for territorial policies intending to meet the challenges of the changes in land use in areas with high urban pressure, where the place of agriculture in territorial development is now questioned.